ROLE AND IMPORTANCE OF INTERNATIONAL ADMINISTRATIVE LAW IN REGULATING THE STATUS OF THE OFFICIALS OF INTERNATIONAL ORGANISATIONS - Glodić, Duško (Politeia, 2024)
The aim of this article is to identify, starting from the theoretical framework for considering the activities of international organizations and relevant institutional practices, the basic factors of the legal status of international officials as established in the rules of international administrative law. The article, first of all, defines the concept of international administrative law. Then, the article clarifies the international legal framework for the autonomous regulation of the status of international civil servants by international organizations, and it analyzes the legal sources of international administrative law. Finally, the article points to the influence that international administrative tribunals had on constituting international administrative law and ensuring its effectiveness. The article demonstrates that the basic features of the international civil service are contained in the fact that international organizations, as independent subjects of international law, autonomously regulate issues of importance for their functioning by adopting their own rules. The article also showed that the effectiveness of international administrative law is ensured through the operations of the international administrative tribunals, as a type of judicial body established within the institutional system of an international organization. The article concludes that international administrative law is particular for each international organization, but that there is a similarity between certain concepts and principles that exist in the rules of various international organizations. Considering importance of the international officials in executing the functions of an international organization, international administrative law, as a legal framework that regulates their position and guarantees their independence from individual governments, is of essential legal relevance for the smooth operation of the international organization as an international legal person.
Keywords: international organizations; international administrative law; law of international organizations; international administrative tribunals